ANALISIS KINERJA KEUANGAN PT UNITED TRACTORS TBK PERIODE 2017 S/D 2020 DENGAN MENGGUNAKAN CURRENT RATIO (CR), RETURN ON ASSET (ROA) DAN DEBT TO ASSET RATIO (DAR) - Sri Wahyuni; Nurman Danil; Muhammad Abdi (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2021)
The purpose of this study was to analyze and determine the financial performance of PT United Tractors Tbk in the period 2017 to 2020 based on the Current Ratio (CR), Return On Assets (ROA) and Debt to Asset Ratio (DAR). The research method used is descriptive method with qualitative research type. The data used is secondary data in the form of the company's annual financial statements obtained from www.idx.co.id and www.unitedtractors.com. The results showed that the company's financial performance as measured by the Current Ratio level showed that the company was in a "Not Good Enough" condition. The Return on Assets level indicates that the company is in a "good" condition and the company's Debt to Asset Ratio level is in a "good" condition.